2001
DOI: 10.1016/s0014-5793(01)03168-4
|View full text |Cite
|
Sign up to set email alerts
|

Depolarisation induces rapid and transient formation of intracellular sphingosine‐1‐phosphate

Abstract: Formation of sphingosine-1-phosphate (SPP) by sphingosine kinase serves as a signalling pathway for various membrane receptors. Here, we show that membrane depolarisation is another mechanism by which this pathway can be activated. Formation of [ 3 H]SPP as well as levels of endogenous SPP were rapidly and transiently increased in PC12 pheochromocytoma cells depolarised with high KCl. Time course and maximum were similar to those induced by bradykinin. Depolarisation-induced SPP production was also observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 36 publications
(89 reference statements)
2
24
0
Order By: Relevance
“…A more recent study demonstrated that membrane depolarization and influx of extracellular Ca 2ϩ increased cellular (PC12 and RINm5F cells) Sphk1-dependent formation of S1P. 15 The current study links these two independent findings to a concept in which downstream the stretch-induced depolarization and subsequent influx of extracellular Ca 2ϩ S1P (depolarization-dependently produced by Sphk1) translates these initial events into a release of Ca 2ϩ from intracellular stores, 10 combined with an activation of the Ca 2ϩ -sensitizing RhoA pathway. Consequently, genetic inhibition of Sphk1 by its dominant negative mutant resulted in significantly attenuated and delayed increases in Ca 2ϩ and only residual myogenic vasoconstrictions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A more recent study demonstrated that membrane depolarization and influx of extracellular Ca 2ϩ increased cellular (PC12 and RINm5F cells) Sphk1-dependent formation of S1P. 15 The current study links these two independent findings to a concept in which downstream the stretch-induced depolarization and subsequent influx of extracellular Ca 2ϩ S1P (depolarization-dependently produced by Sphk1) translates these initial events into a release of Ca 2ϩ from intracellular stores, 10 combined with an activation of the Ca 2ϩ -sensitizing RhoA pathway. Consequently, genetic inhibition of Sphk1 by its dominant negative mutant resulted in significantly attenuated and delayed increases in Ca 2ϩ and only residual myogenic vasoconstrictions.…”
Section: Discussionmentioning
confidence: 97%
“…The activity of the S1P-generating enzyme Sphk1 is increased by membrane depolarization and activation of voltage-gated Ca 2ϩ channels. 15 Both effects are known to be essential for MRs, 13 leading us to hypothesize that Sphk1 is a part of the pressure-induced signaling cascade. To study a potential role of Sphk1 for this transduction pathway, we used a new transfection model to overexpress Sphk1 16 and its dominant negative mutant hSK-G82D 17 in VSMCs of isolated RAs.…”
mentioning
confidence: 99%
“…Several reasons may contribute as to why: (1) it potentially allows for localization to plasma membrane microdomains (eg, caveolae), which are enriched with its substrate, sphingosine, and offer the opportunity to cluster with other S1P-related signaling components; (2) localization to the membrane would be a necessary prerequisite for the previously described export of S1P and/or Sk1 20 ; and (3) exposure of Sk1 to alterations in electric potential, which may modulate its activity, 21 can only occur at the plasma membrane. We therefore aimed to bypass the translocation deficiency of the Sk1 S225A mutant by the addition of a myristoylation/palmitylation motif that acts as a membrane anchor (mp-Sk1 S225A ).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, resting tone did not differ between the 2 groups ( Figure 5B). Following depolarization, which activates Sk1, 20 H208A ( Figure 5C). H208A in resistance arteries had no effect on myogenic vasoconstriction (B), diameter/Ca 2ϩ relationship (C), or the dose-response curve (D) to exogenous S1P (for graphs B through D, nϭ5 for control and nϭ8 for SPP1 H208A groups).…”
Section: Spp1 Wt Antagonizes Enhanced Vascular Responsiveness In Sk1 mentioning
confidence: 99%
“…This may represent a methodological limitation whereby measurement of S1P-induced increases in Ca sensitivity are compromised by the intrinsic sensitivity of Sk1 to depolarizing stimuli. The depolarizing conditions required to clamp intracellular Ca 2ϩ (via extracellular Ca 2ϩ ) may activate Sk1 20 and stimulate the release of S1P (or activate other Ca 2ϩ -sensitizing mechanisms) such that measurement occurs under conditions of near-maximal Ca 2ϩ sensitivity. This is in accordance with one of our previous observations, where exogenously applied S1P also failed to left shift the Ca 2ϩ -sensitivity curve under these specific experimental conditions.…”
Section: ϫ8mentioning
confidence: 99%